Implementation of a mHealth solution to remotely monitor patients on a cardiac surgical waiting list: service evaluation. Issue 3 (4th August 2021) - Obika, Bernard Dillon; Dolezova, Nikola; Ponzo, Sonia; Valentine, Sophie; Shah, Sachin; Gledhill, Jonathan; Plans, David; Nicholson, Conor; Walters, Cathy; Stephen, Laura; Ng, Serena; Ayres, Janet; et al.
Abstract: Background: The emergence of COVID-19 resulted in postponement of nonemergent surgical procedures for cardiac patients in London. mHealth represented a potentially viable mechanism for highlighting deteriorating patients on the lengthened cardiac surgical waiting lists. Objective: To evaluate the deployment of a digital health solution to support continuous triaging of patients on a cardiac surgical waiting list. Method: An NHS trust utilized an app-based mHealth solution (Huma Therapeutics) to help gather vital information on patients awaiting cardiac surgery (valvular and coronary surgery). Patients at a tertiary cardiac center on a waiting list for elective surgery were given the option to be monitored remotely via a mobile app until their date of surgery. Patients were asked to enter their symptoms once a week. The clinical team monitored this information remotely, prompting intervention for those patients who needed it. Results: Five hundred and twenty-five patients were on boarded onto the app. Of the 525 patients using the solution, 51 (9.71%) were identified as at risk of deteriorating based on data captured via the remote patient monitoring platform and subsequently escalated to their respective consultant. 81.7% of patients input at least one symptom after they were on boarded on the platform. Discussion: Although not a generalizable study, this change in practice clearly demonstrates the feasibility and potential benefit digital remote patient monitoring can have in triaging large surgical wait lists, ensuring those that need care urgently receive it. We recommend further study into the potential beneficial outcomes from preoperative cardiac mHealth solutions.